A PLAG1 mutation contributed to stature recovery in modern cattle. Issue 1 (December 2017) - Utsunomiya, Yuri; Milanesi, Marco; Utsunomiya, Adam; Torrecilha, Rafaela; Kim, Eui-Soo; Costa, Márcio; Aguiar, Tamíris; Schroeder, Steven; Carmo, Adriana; Carvalheiro, Roberto; Neves, Haroldo; Padula, Romulo; et al.
Abstract The recent evolution of cattle is marked by fluctuations in body size. Height in theBos taurus lineage was reduced by a factor of 1.5 from the Neolithic to the Middle Ages, and increased again only during the Early Modern Ages. Using haplotype analysis, we found evidence that the bovinePLAG1 mutation (Q ) with major effects on body size, weight and reproduction is a >1, 000 years old derived allele that increased rapidly in frequency in Northwestern EuropeanB. taurus between the 16th and 18th centuries. Towards the 19th and 20th centuries, Q was introgressed into non-EuropeanB. taurus andBos indicus breeds. These data implicate a major role ofQ in recent changes in body size in modern cattle, and represent one of the first examples of a genomic sweep in livestock that was driven by selection on a complex trait.